351 Claudin 6 Expression in Atypical Teratoid/Rhabdoid Tumors is a Target for CAR-T Cell Therapy. (April 2023) - Madsen, Peter J.; Stern, Allison; Griffin, Crystal; Oehm, Petr; Rengstl, Benjamin; Flemmig, Carina; Tucker, Alexander; Storm, Phillip B.; Resnick, Adam C.; Foster, Jessica
Abstract : INTRODUCTION: Novel therapies for atypical teratoid/rhabdoid tumor (ATRT) are desperately needed. Claudin-6 (CLDN6) is a tight junction protein present during early development and in some tumors, but not at appreciable levels in normal tissue. CLDN6-targeted chimeric antigen receptor (CAR) T cells with a CAR-T cell–amplifying RNA vaccine have demonstrated antitumor activity against CLDN6-expressing cancers in pre-clinical and clinical trials (NCT04503278; Haanen J et al AACR, 2022). METHODS: CLDN6 expression was assessed on primary ATRT specimens by RNAseq and immunohistochemistry and on tumor-derived cell lines by flow cytometry. CLDN6-positive and negative cell lines were co-cultured with CLDN6-targeting CAR-T cells and killing efficacy was measured. A second-generation mRNA CAR with a 4-1BB costimulatory domain and single-chain variable fragment directed against CLDN6 was used (Reinhard et al, 2020). Cell lines were modified with reporter assays and intracranial xenografts were created in NSG mice. RESULTS: 50% of specimens had CLDN6 expression greater than 2 FPKM (N = 28). Immunohistochemistry was positive in 53% of specimens (N = 15). Multiple CLDN6-positive ATRT cell lines were identified by flow cytometry. Co-culture of CLDN6-directed mRNA CAR-T cells with ATRT line 7316-2187 resulted in tumor-specific cytotoxicity versus CD19-directed control CAR-T cells (92% versus 15% at 10:1, p < 0.0001; 86% versus 0% at 5:1, p < 0.0001). Similar results were seen with an additional CLDN6-positive ATRT cell line 7316-2141 (75% versus 7% at 10:1, p < 0.0001; 53% versus 0% at 5:1, p < 0.0001). Both CLDN6- and CD19-directed CAR-T cells showed no cytotoxicity against a CLDN6-negative cell line, 7316-4149. Xenografts were successfully created, and ongoing work is evaluating locoregional administration of CLDN6-directed CAR-T cells. CONCLUSIONS: This work highlights the potential of targeting CLDN6 with CAR-T cell therapy as a novel treatment strategy for patients with ATRT.